Application of participatory design to development of organic farming game based on the philosophy of sufficiency economy - Sangsuwan, Watcharakiti; Sae Lee, Suebsiri (Creative Science, 2019)
This study aimed to: 1) explore the Philosophy of Sufficiency Economy and theparticipatory designfor developing theorganic farming lifesimulation game; 2) develop the organic farming life simulation game based on the Philosophy of Sufficiency Economy; and 3) evaluate the functional quality of the prototype simulation game. In this study, the researcher focused on the literature review onthe related documents and supportive theories throughthe theoretical framework ofHuman-Centre Design (HCD)that primarily emphasizesthe stakeholder’s benefits. The researcher also gave deeperattention onthe procedure and background context ofthesupportive theories in order toconstruct the research conceptual frameworkand another theory applied in this study wasthe Participatory Design (PD). The document data wasdeducted from the literature review and the field data for the game content was derivedfrom the expert and the sample groupincluding: 1) the organic farmers; 2) the agriculturists; and 3) the agricultural administrativeand the sample group from Khon Kaen Vocational College divided into 28 vocational certificate students and 32 high vocational certificate students.In term of the user’s need for the gamedesign, the data wasanalyzed and interpreted to definethe final result for thedesiredcontent and other feature designs for the organic farming game following the Philosophy of Sufficiency Economy and this final result was used to create the game through theGame Design Document Outline (GDD). Then, the data set derived from the final result was used to design the game to beevaluated with the 5-point rating scale evaluation by 5 media experts and 100 students from Khon Kaen Vocational College. Theoutcome indicated that the quality of the game was good (ݔ̅= 3.93, S.D. = 0.45)and when comparing with the standard mean initially defined at3.51,itwas higher so thatthe game wasensuredto be applicable for practical use.